Character Education from Thomas Lickona’s Perspective in Building Moral Intelligence in Primary Education - Putri Anisa; Rina Rahmi; Maya Agustina; Muhammad Azhari; Hawa Hazwanie Yacob (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
This study aims to analyze the implementation of character education based on Thomas Lickona’s perspective in building moral intelligence in primary education. The study addresses the gap between theoretical concepts of character education and their practical application in school settings. Using a qualitative case study approach conducted at SRITI Al-Qawwam, data were collected through observation, in-depth interviews, and documentation. The findings show that character values such as discipline, responsibility, empathy, and respect are integrated into daily learning activities, school culture, and teacher-student interactions. Teachers act as role models while reinforcing values through habituation and reflective communication. However, challenges remain, including limited teacher competence in moral pedagogy, time constraints, and the influence of digital environments. This study contributes to strengthening the practical application of Lickona’s framework in developing students’ moral intelligence.